2021
DOI: 10.3389/fcvm.2021.702780
|View full text |Cite
|
Sign up to set email alerts
|

Antithrombotic Treatment After Surgical and Transcatheter Heart Valve Repair and Replacement

Abstract: New antithrombotic drugs have been developed, new valve types have been designed and minimally invasive transcatheter techniques have emerged, making the choice of antithrombotic therapy after surgical or transcatheter heart valve repair and replacement increasingly complex. Moreover, due to a lack of large randomized controlled trials many recommendations for antithrombotic therapy are based on expert opinion, reflected by divergent recommendations in current guidelines. Therefore, decision-making in clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 59 publications
0
13
0
Order By: Relevance
“…In surgery and transcutaneous procedures, a vascular closure device is safe to use and allows for the percutaneous cannulation of the femoral vessels [ 40 ]. Verstraete et al in 2021 provided a useful review with a variety of considerations for antithrombotic treatment after surgery and transcutaneous procedures [ 41 , 42 ]. The use of direct oral anticoagulants (DOACs) is the subject of ongoing studies, although occasional studies have shown MIMVS to have promising results [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…In surgery and transcutaneous procedures, a vascular closure device is safe to use and allows for the percutaneous cannulation of the femoral vessels [ 40 ]. Verstraete et al in 2021 provided a useful review with a variety of considerations for antithrombotic treatment after surgery and transcutaneous procedures [ 41 , 42 ]. The use of direct oral anticoagulants (DOACs) is the subject of ongoing studies, although occasional studies have shown MIMVS to have promising results [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, Observational studies suggest that VKAs are not superior to low‐dose aspirin regarding thromboembolic prevention after mitral valve repair, but potentially increase the risk of bleeding. After aortic valve repair, low‐dose aspirin can be considered as per current recommendations 10 …”
Section: Discussionmentioning
confidence: 99%
“…Although these patients were included in multiple groups, the presence of combination therapy was included as a potential confounder in the regression models to account for this. The initiation and duration of treatment with antithrombotic therapies in the PVE group at our center has been published prevoiusly 13 ; details are given in the Appendix E1 .…”
Section: Methodsmentioning
confidence: 99%
“…Some patients received 2 or more antithrombotic therapies; these are summarized in Table E2. Although these patients were included in multiple groups, the presence of combination therapy was included as a potential confounder in the 13 ; details are given in the Appendix E1.…”
Section: Study Design and Objectivesmentioning
confidence: 99%